2016
DOI: 10.1590/s0100-204x2016000900021
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen oxides and CO2 from an Oxisol cultivated with corn in succession to cover crops

Abstract: -The objective of this work was to evaluate the effect of two legumes (Crotalaria juncea and Mucuna pruriens), as cover crops, and of natural fallow, as a control treatment, on the emissions of NO x , N 2 O, and CO 2 from an Oxisol cultivated with corn, under conventional and no-tillage systems, in the Cerrado region, in Central Brazil. Variations of CO 2 fluxes in the soil were explained mainly by soil humidity and, in the legumes, under conventional system, by soil NH 4 + -N concentration. Plots with legumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…In addition, no significant differences between all phases on cumulative CO 2 fluxes were found, results that may be due to the absence effect of crop rotational diversity on soil temperature over the study period. However, Carvalho et al [56], Rochette and Janzen [57] and Brock et al [58] reported that the decomposition of the previous crop residues in the crop rotation can influence GHG fluxes. Other parameter that could influence soil respiration included SOC; however, there was no significant effect on SOC by crop rotational diversity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no significant differences between all phases on cumulative CO 2 fluxes were found, results that may be due to the absence effect of crop rotational diversity on soil temperature over the study period. However, Carvalho et al [56], Rochette and Janzen [57] and Brock et al [58] reported that the decomposition of the previous crop residues in the crop rotation can influence GHG fluxes. Other parameter that could influence soil respiration included SOC; however, there was no significant effect on SOC by crop rotational diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The input of foliar N from leguminous tree leaves in the AFS influenced soil N dynamics in the studied AFS. Consequently, the high input of foliar N contributed to decreasing litter C:N ratio and facilitated litter decomposition, associated to considerable N2O fluxes with significant loss of N to the atmosphere compared to native Cerrado vegetation (Carvalho et al, 2016). Those indicators of the short-term N dynamics in the AFS are reflected in the soil δ 15 N, providing indirect evidence of N intensification in the soil-plant-litter system in the AFS.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be considered that the transformations of N in an ecosystem (immobilization or mineralization) are coupled to C transformations, especially when organic carbon molecules are converted into CO2 by soil heterotrophic microbial populations (McGill e Cole, 1981), which can reduce the partial pressure of oxygen and favor denitrification. Significant N2O pulse emissions following the first rains after a dry season, often with a small-time lag, have been reported for different seasonally dry ecosystems and are generally preceded by significant CO2 emissions immediately after the soil is re-moistened, due to water-induced activation of soil microbes (Carvalho et al, 2016;Carvalho et al, 2017;Sato et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different factors affecting N 2 O emissions in agricultural soils, the conversion of native Cerrado vegetation to agroecosystems favors the emission of N 2 O to the atmosphere, under sugarcane cropping systems (Silva et al, 2017), integrated cropping-livestock production, no-till and conventional tillage (Martins et al, 2015;Sato et al, 2017). In addition, N 2 O emissions are usually associated with soil moisture (Carvalho et al, 2013;Santos et al, 2016) and nitrogen fertilizer application (Carvalho et al, 2016;Silva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%